Research article Sero-prevalence and risk factors for hepatitis B virus infection among health care workers in a tertiary hospital in Uganda - Ziraba, Abdhalah K.; Bwogi, Josephine; Namale, Alice; Wainaina, Caroline W.; Mayanja-Kizza, Harriet (BMC infectious diseases, 2010)
Hepatitis B virus (HBV) infection is a global public health challenge. Prevalence of current hepatitis B virus infection in the general population in Uganda is about 10%. Health care workers (HCW) have an extra risk of getting infected from their workplace and yet they are not routinely vaccinated against HBV infection. This study aimed at estimating prevalence of hepatitis B virus infection and associated risk factors among health care workers in a tertiary hospital in Uganda. Methods: Data were obtained from a cross sectional survey conducted in Mulago, a national referral and teaching hospital in Uganda among health care workers in 2003. A proportionate to size random sample was drawn per health care worker category. A structured questionnaire was used to collect data on socio-demographic characteristics and risk factors. ELISA was used to test sera for HBsAg, anti-HBs and total anti-HBc. Descriptive and logistic regression models were used for analysis.
Keywords: Sero-prevalence; Hepatitis B virus infection; Health care workers; Tertiary hospital